The distribution of dividend on the shareholders’ wealth: an analysis between Government Linked Companies and family based companies (2004 – 2013) / Siti Hafizah Harun - Harun, Siti Hafizah (2015)
The purpose of the study is to examine the distribution of dividend policy on shareholders wealth. To be more details, this research wants to compare between Government Linked Companies (GLCs) and Family Based Companies (FBCs) in terms of the impact of dividend distribution to each type of companies. Ten companies that were listed in Bursa Malaysia were selected based on their rankings in terms of operating turnover for the year 2013. All data were derived from the OSIRIS database, Data Stream, Bursa Malaysia and annual reports; consists of five GLCs and five FBCs. This research is also meant to investigate the relationship between the three independent variables namely retained earnings (RE), dividend per share (DPS) and earnings per share (EPS) with the market price per share (MPS). The findings show that there is different factor that can influence the level of MPS for both GLCs and FBCs. For Government Linked Companies only dividend per share that has a significant relationship with share price and for Family Based Companies only earning per share has a significant relationship with share price. Furthermore, Dummy variables is used to measured the differences in each group between GLCs and FBCs. Based on the above result, it shows p-value of this variable is 0.402 which at 5% significant level. In other words, there is no evidence to show whether GLCs is getting higher earnings as compared to the FBCs. Due to such evidence, the second model can be used to analysed the differences in terms of their earnings.